An Inverted-Sandwich Dichromium(I) Complex Stabilized by Guanidinate Ligands - Awal Noor; Sadaf Qayyum; Andre Dickert; Mohamed El Oirdi (Molbank)
Reduction of the four-coordinate “ate” species [(RC(NAr)2Cr(µ-Cl)2Li(THF)2] (1) (R = diisopropylamine; Ar = 2,6-diisopropylphenyl) with potassium graphite (KC8) in toluene leads to the formation of a toluene-bridged inverted-sandwich dichromium(I) complex, (µ-η6:η6-C7H8)[Cr{RC(NAr)2}]2 (2). X-ray analysis confirms the dinuclear nature of (2). The compound [C69H104Cr2N6], crystallized in the monoclinic space group, P21/c, has the following cell parameters: a  =  15.108(3) b  =  29.155(6) c  =  17.486(4) Å, β  =  101.19(3)°, V  =  7555(3) A3, and Z  =  4.